The contribution of Pegadaian’s gold to public finances: A bibliometric and SEM-PLS analysis - Wahyu Almizri; Yusuf Akhmad (Journal of Sustainability, Society, and Eco-Welfare, 2026)
Background: Financial inclusion is a fundamental pillar of global sustainable development, yet achieving universal access remains a challenge in many emerging economies due to a persistent digital divide and structural barriers. While global discourse has shifted toward digital-centric solutions, conventional asset-based instruments like gold pawning which leverage high levels of physical gold ownership remain vital at the grassroots level. This study aims to analyze the strategic contribution of gold pawning to financial inclusion by bridging the gap between global research trends and empirical field realities. Methods: Utilizing a mixed-methods exploratory sequential design, the study first employs bibliometric analysis on 208 scientific publications (2015–2025) retrieved via Publish or Perish to map the intellectual structure of the field. This is followed by a quantitative empirical analysis of 101 respondents using structural equation modeling–partial least squares (SEM-PLS) to test the causal relationship between gold pawning and financial inclusion. Findings: The bibliometric mapping reveals a dominant global shift toward digital finance and fintech, identifying gold pawning as a "missing link" that is relatively underrepresented in scholarly literature despite its practical usage. The refined empirical model demonstrates that gold pawning exerts a strong positive effect on financial inclusion with a path coefficient of 0.761. The model exhibits substantial predictive power with an R-square (R2) of 0.512 and an exceptionally large effect size (f2) of 1.050, indicating that gold pawning is a primary driver for expanding access to the formal financial system. Conclusion: These findings confirm that gold pawning serves as a context-sensitive and high-trust "gateway" for the unbanked, minimizing barriers related to digital literacy and documentation; strengthen social welfare at the grassroots level by providing immediate liquidity, enhancing financial resilience, and bridging socioeconomic gaps without the barrier of digital literacy. Novelty/Originality of this article: This study contributes to the field of ecosocial well-being by empirically identifying traditional asset-based financing as a crucial link that has long been overlooked in sustainable financial inclusion.